Human Herpesvirus 6 and Chronic Fatigue Syndrome - Daniel Eymard; François Lebel; Mark Miller; François Turgeon (Canadian Journal of Infectious Diseases)
The cause of chronic fatigue syndrome (CFS) is still enigmatic. Using indirect immunofluorescence testing for measuring antibody against human herpesvirus 6 (HHV-6), this study investigated the association of CFS with infection by HHV-6. Seventeen patients (group A) fulfilling the Centers for Disease Control (CDC) definition for CFS were compared with eight patients (group B) with chronic fatigue but not meeting the CDC criteria. No significant difference was found between the two groups for 30 parameters including sex, age, exposure to children and serology for Epstein-Barr virus, cytomegalovirus, herpes simplex virus, and toxoplasma. Univariate analysis showed that patients in group A complained more frequently of a sore throat, headache and of recurrent type of fatigue. These three parameters are discriminant in identifying patients who will meet the CDC case definition of CFS. The titre of antibody against HHV-6 in group A (1:99) was significantly higher than in group B (1:15) (P=0.007). Elevated HHV-6 titres suggests that this virus could be a cofactor in the pathogenesis of CFS.